Determining Groundwater Recharge from Stream Flow with Seasonal Recession Method - Ichwana -; Zulkifli Nasution; Sumono - (Aceh International Journal of Science and Technology, 2013)
Abstract - Volume of groundwater recharge showed a picture of a watershed to determine the flow instability due to the physical characteristics of the watershed and precipitation. Many methods had been constructed to understand the dynamic movement of water discharge. One of them was the analysis of the stream hydrograph with Seasonal Recession Method. Information about groundwater recharge condition at several sub watershed in Krueng Peusangan Watershed was really needed in management of watershed for sustainable water resources. The study aimed to determine groundwater recharge from stream flow with seasonal recession method was conducted in Krueng Peusangan watershed, Aceh Province, Indonesia. The results showed that the trend pattern of the stream hydrograph could be explained using the exponential function where the dots lowest discharge that is the end of the recession (y) than any period of time on stream hydrograph semi logarithmic (x). The pattern of results that occurred in the watershed of Krueng Peusangan: (A) Krueng Seumpo had a trend for y = 9.2x-0.35, (B) Simpang Jaya  for y = 559.7x-0.5, (C) Beukah village for y = 142x-0.32 , (D) Sub watershed of Lut Tawar (Wih Nareh) for y = 1.3x-0.12 and (E) Sub watershed of Teupin Mane (Krueng Teumbo) for y = 1.94x-0.42. It also showed that the location of A, B, C, E had a higher slope and a decreased recharge pattern compared to the location of D (sub watershed of  Lut Tawar)  that tended to flat. The volume of groundwater recharge that occurred in a region (A and D) increased while the other location was very volatile. Moreover, recharge instability occurred in Krueng Teumbo. Therefore, it needed a clear direction for land use and functions of forests, especially in the recharge area, in order to maintain the balance of the hydrological cycle, and the quantity of groundwater. Keywords: groundwater recharge, seasonal recession method, base flow, stream flow, water resources